Analisis Standardisasi Laboratorium Dalam Proses Pembelajaran Fisika (Studi Kasus Di SMA 4 Langsa) - Nur Jannah Berutu; Deviona Aurora; Rini Amalia; Riska Amelza; Tarzky Adinda Siregar; Nur Azizah Lubis (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2023)
The research included the head of the laboratory, laboratory staff, physics teacher, students, and physics laboratory facilities at SMA Negeri 4 LANGSA as subjects. Data collection techniques comprised observation sheets, questionnaires, interview guides, and documentation. The study's results encompassed interviews conducted with the head of the laboratory, physics teachers, and students. These findings will be presented in a table format. Based on observations at SMAN 4 Langsa, the laboratory equipment was deemed relatively good, with nearly 80% completeness. Consequently, it can be concluded that the standardization of the physics laboratory's facilities and infrastructure at SMAN 4 Langsa is close to meeting good standards due to its sufficient facilities and infrastructure. However, the standardization of physics laboratory management competency at SMAN 4 Langsa is not fully compliant with the regulations outlined in the Minister of National Education of the Republic of Indonesia's No. 26 of 2008. Additionally, the effectiveness of utilizing physics laboratory facilities and infrastructure at SMAN 4 Langsa indicates poor quality.